Fatherhood, manhood, and personhood: South African fathers' experiences of parental identity development - Divine, Wayela Bitalo; Piotrowski, Konrad; Naudé, Luzelle (Journal of family studies, 2024)
Fatherhood is rooted in various cultural, societal, and even religious belief systems. In the South African context, where fathers are often perceived to be absent or uninvolved, fathers' parental identity development might be hindered. This study focused on fathers' commitment, exploration, and reconsideration in the process of forming a parental identity within the South African sociocultural context. Eight emerging and early adult black South African fathers were interviewed. Through reflexive thematic analysis, a nuanced visage of fatherhood that carries both the old ideologies of material provision and the newfound valuing of nurturing care was constructed. The complexities of balancing ideas of fatherhood, manhood, and personhood were evident in how participants struggled to align their aspirations of being physically present and emotionally engaged fathers with the reality of being providers in a financially strenuous context. Participants embraced the idea of a family unit as a foundation and also appreciated the value of communal notions of childrearing. While the challenging nature of fatherhood was often met with reconsideration, a firm commitment was evident. This qualitative inquiry into the experiences of fatherhood addresses the personal, socio-economic, and cultural aspects embedded in the formation of parental identity among black South African men.